Single-Use Technology : A Practical Guide to Design and Implementation - Lopes, Adriana G.; Brown, Andrew (De Gruyter STEM, 2019)
Single-Use Technology (SUT) is the first comprehensive publication of practical considerations for each stage of the implementation process of SUT, and covers the selection, specification, design and qualification of systems to meet end-user requirements. Having become readily available for all processing operations within the biopharmaceutical industry, SUT has the potential to reduce capital costs, improve plant throughput and reduce the risk of cross-contamination. However, there are no clear guidelines to aid the end-user on implementation of these technologies into a validated, good manufacturing practice (GMP) environment. This book presents approaches for the implementation within various end-user facilities and systems, SUT within regulatory frameworks (ICH Q8, Q9, Q10 and GMP), standardisation and assessment strategies, specifation of user requirements and SUT design, risk assessment and evaluation as well as qualification for different SUT types.